Legalisation of e-scooters in the UK: the injury rate and pattern is similar to those of bicycles in an inner city metropolitan area. (May 2022) - Bodansky, D.M.S.; Gach, M.W.; Grant, M.; Solari, M.; Nebhani, N.; Crouch-Smith, H.; Campbell, M.; Banks, J.; Cheung, G.
Abstract: Introduction: Rental electric scooters (e-scooters) have become more available to the UK public following amendments to legislation in 2020 affecting rideshare schemes. Existing literature from outside the UK demonstrates a worrying trend of increasing injuries related to their use and non-compliance with suggested safety precautions. An e-scooter rideshare scheme trial began in Liverpool in October 2020. We intended to identify the musculoskeletal injury rate and describe the injuries sustained during this pilot. Methods: Data were collected retrospectively from electronic patient records on all patients at a major trauma centre covering the whole of the Liverpool rideshare trial site presenting with e-scooter and bicycle musculoskeletal injuries between the trial start on 6th October 2020 and 5th May 2021 and between 6th March 2020 and 5th October 2020. Data on rental e-scooter use were obtained from the rideshare operator. Results: Fifty-one patients sustained musculoskeletal injuries involving e-scooters during the trial period and six injuries before the trial. Two-thirds of injuries were on rental e-scooters. We calculate an orthopaedic injury rate of 26.1 injuries per million km on e-scooters and 24.1 injuries per million km on bicycles. Over 70% of e-scooter patients had upper limb injuries, over 50% had lower limb injuries and 15.7% of patients required surgery. Conclusions: We observed an increase in musculoskeletal injuries presenting to hospital during the e-scooter pilot. Rates of musculoskeletal injuries were comparable to rates of injuries sustained on bicycles. E-scooters should be regulated closely and further safety measures introduced to minimise the rate of injuries.